2013
DOI: 10.1371/journal.pone.0053762
|View full text |Cite
|
Sign up to set email alerts
|

The NifA-RpoN Regulon of Mesorhizobium loti Strain R7A and Its Symbiotic Activation by a Novel LacI/GalR-Family Regulator

Abstract: Mesorhizobium loti is the microsymbiont of Lotus species, including the model legume L. japonicus. M. loti differs from other rhizobia in that it contains two copies of the key nitrogen fixation regulatory gene nifA, nifA1 and nifA2, both of which are located on the symbiosis island ICEMlSymR7A. M. loti R7A also contains two rpoN genes, rpoN1 located on the chromosome outside of ICEMlSymR7A and rpoN2 that is located on ICEMlSymR7A. The aims of the current work were to establish how nifA expression was activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 67 publications
1
27
0
1
Order By: Relevance
“…A comparative study of 1,300 LacI transcription factors found that nearly 90% of these were local regulators of sugar utilization pathways, with regulatory effects impacting only genes located near the regulator gene in the genome, while the other 10% of LacI regulators control large sets of genes and are considered to be global regulators. LacI family members can also be integrated into complex regulatory networks, as is the case for Mesorhizobium loti FixV, which activates genes for symbiotic nitrogen fixation (33), as an example.…”
Section: Discussionmentioning
confidence: 99%
“…A comparative study of 1,300 LacI transcription factors found that nearly 90% of these were local regulators of sugar utilization pathways, with regulatory effects impacting only genes located near the regulator gene in the genome, while the other 10% of LacI regulators control large sets of genes and are considered to be global regulators. LacI family members can also be integrated into complex regulatory networks, as is the case for Mesorhizobium loti FixV, which activates genes for symbiotic nitrogen fixation (33), as an example.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the outer membrane protein (gi|13475117) encoded by mll6127 was also identified in a previous study of the Lotus symbiosome membrane and is essential for efficient nitrogen fixation . Several of the other identified proteins are also encoded on the symbiosis island but the regulation of the corresponding genes ( mlr5787 , mll5810 , mll5998 , mll6062 , mlr6296 ) has not been reported.…”
Section: Resultsmentioning
confidence: 91%
“…Several of the identified M. loti proteins are encoded on the symbiosis island . Many of the corresponding genes are directly regulated by the master regulator NifA and are strongly expressed in bacteroids, including mll5873 ( msi334 in M. loti strain R7A), mlr5906 ( nifD ), mlr5907 ( nifK ), mlr5932 ( acdS ), mlr5943 ( msi260 ), mlr5944 ( msi259 ), and mll6127 ( msi158 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Both GI and GII ICESyms contained a three-gene cluster preceded by a nifA-regulated promoter, which consists of a hypothetical DUF683-containing gene followed by fdxB-syrA [84]. The SyrA protein has previously been implicated in the post-translational regulation of exopolysaccharide (EPS) production in Sinorhizobium meliloti [85].…”
Section: Putative Host-range Determinants Conserved In Broad-host-ranmentioning
confidence: 99%